A new deployment method for electric vehicle charging infrastructure - Yagcitekin, Bunyamin; Uzunoglu, Mehmet; Karakas, Arif (Tubitak Scientific & Technological Research Council Turkey, 2016)
The fast depletion of fossil fuels, climate change, and global warming have become major worldwide problems and alternatives for conventional transportation have been actively researched in the last decade. Compared to available conventional vehicles, electric vehicles have a leading position due to their environmentally friendly transportation. Recent electric vehicle penetration brings the necessity of a high number of charging stations, which are considered to be established in community areas such as shopping centers, hospitals, commercial areas, university campuses, residential areas, and streets. Deployment planning of charging stations is very important for driver expectations and social and economic impacts of electric vehicles. In this regard, optimizing the number of charging stations and their locations is very important for wide-scale use of electric vehicles. Including a new criterion into the existing charging station planning methods is difficult. Due to their structural characteristics, a new flexible planning model of charging stations is needed. In the new model, the queue theory and the analytic hierarchy process are used together to develop a mathematical model for both optimizing the number of charging stations and choosing the best charger locations in a selected region. A case study is performed to show the suitability of the proposed model for finding the optimum location and number of charging stations by evaluating survey data, which reflects drivers' habits within a university campus.
Keywords: Electric vehicle; charging station; charging infrastructure planning; decision making; optimization; LOCATION; STATIONS; MODEL; Computer Science; Engineering